Experimental study on flexural behavior of NSM and external bonded FRP strengthened pretensioned precast hollow core slabs - Pachalla, Sameer Kumar Sarma; Dhara, J. Suman; Prakash, S. Suriya (Journal of Structural Engineering, 2024)
Prestressed Precast Hollow Core (PPHC) slabs are floor/roof elements which have longitudinal cores along the span. Strengthening of these slabs may be required for several reasons. The objective of this study is to understand the flexure and flexure-shear behavior, failure mechanisms of PPHC slabs with and without Fiber-Reinforced Polymer (FRP) strengthening. Experimental variables include (i) different FRP strengthening techniques, namely External Bonding (EB) and near-surface mounting (NSM), (ii) strengthening reinforcement ratios and (iii) shear span to depth (a/d) ratios. Test results revealed that the FRP strengthening is very effective in increasing the ultimate strength of slabs and strengthening changed the failure modes of the slabs. Experimental results show that the flexural load carrying capacity of PPHC slabs increased in the range of 14% to 36% depending on the strengthening scheme used. It was found that Near Surface Mounted (NSM) flexural strengthening ratio should be carefully selected to avoid unfavorable brittle shear failure. Interesting transition from flexure to the flexure-shear failure of the slabs was noted in the behavior as the FRP strengthening ratio was increased.